“Gifts of Light”—Chiara Lubich’s Mystical Narrative with Hindus: An Analysis of a Hindu–Christian Dialogue Experience - Roberto Catalano (Religions, 2023)
The present paper offers a presentation and a phenomenological analysis of a rather unusual event in the sphere of interreligious dialogue: a Catholic woman, the protagonist of a mystical experience, shared some of the traits of this experience with people of another culture and religion. The protagonists of this experience include Chiara Lubich and a group of Hindus, some neo-Vedanta scholars and other social activists inspired by Gandhian philosophy and ideals. These pages represent an initial study of this case, which, at least so far, appears to be rather unique.